Digital Phonics Ecosystem: Implementation of a Digital Learning Environment to Improve Reading Literacy in Madrasah Ibtidaiyah Students - Muhammad Mushfi El Iq Bali; Arini Ayati Robby (MAGISTRA: Media Pengembangan Ilmu Pendidikan Dasar dan Keislaman, 2026)
The development of digital technology demands innovation in reading instruction at Madrasah Ibtidaiyah, as conventional methods often cause students to become bored quickly and lack active engagement. The low reading ability at Madrasah Ibtidaiyah Nurul Mun’im indicates the need for an interactive and contextual digital phonics ecosystem solution. This study aims to describe the implementation of the Digital Phonics Ecosystem assisted by Wordwall media in early reading learning, analyzing its contribution to improving student literacy. The research method used was descriptive qualitative with a case study type, while the data collection techniques included observation of learning activities, interviews with teachers, photo documentation, and early reading tests to measure students’ time efficiency and accuracy. The research steps included mapping the initial learning conditions, designing phonics-based Wordwall media, implementation in grade II, and analysis of student learning outcomes. The results showed a significant improvement in early reading skills marked by a decrease in the average reading time from 10 minutes to 6 minutes and all students being able to answer questions correctly. The findings also showed student enthusiasm and collaboration during learning, while the researcher’s assistance played a role in ensuring the use of digital media and the teacher’s role in adjusting strategies to student abilities. The success of the Digital Phonics Ecosystem depends not only on technology but also on the synergy between teacher guidance and researcher support. This study affirms the potential of the Digital Phonics Ecosystem as an interactive and contextual digital-based phonics learning model to improve reading literacy in Madrasah Ibtidaiyah.